EFFECT OF NITROGEN SOURCE AND INITIAL SUGAR CONCENTRATION ON LACTIC ACID FERMENTATION OF PINEAPPLE WASTE USING L.DELBRUECKII - Abdullah Moch Busairi (TEKNIK, 2010)
The liquid pineapple waste contains mainly sucrose, glucose, fructose and other nutrients. It therefore can potentially be used as carbon source for lactic acid fermentation. The lactic acid is utilised in food technology as pH regulator, microbial preservative, buffering agent and in the chemical industry. Recently, lactic acid has been considered to be an important raw material for production of biodegradable lactate polymer. The experiments were carried out in batch fermentation at anaerobic condition with stirring speed: 50 rpm, temperature: 40 oC, pH: 6.0, and inoculum size: 5%. Effect of nitrogen source and initial sugar concentration were studied. The effect of nitrogen source on lactic acid production shows that the yeast extract is highest yield , followed by urea , corn steep liquor, malt sprout and ammonium sulphates with the yield of 78.52; 26.68; 19.14; 14.10 and 5.6 %, respectively. The highest yield of initial sugar concentration on lactic acid production obtained was 78.52 % (54.97 g/l) at 70 g/l, if the concentration of sugar was increased to 110 g/l , the lactic acid production or yield decrease to51.53 g/l or 54.24%.